Nilai-nilai Pendidikan dalam Tradisi Peresean: Kajian Etnopedagogik Masyarakat Lombok - Mudarman; Al-Pansori, Muh. Jaelani; Rismawati, Lia (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2024)
This article aims to examine the educational values embedded in the Peresean tradition of the Sasak community in Lombok and its relevance in character development for students. Using an ethnopedagogical approach, this study explores how values such as bravery, sportsmanship, self-control, and responsibility are transmitted through this tradition. The research employs a qualitative method with a case study approach. Data were collected through participatory observation, in-depth interviews with community leaders, participants, and locals, as well as documentation of Peresean events. The findings indicate that the Peresean tradition has significant potential as a holistic medium for character education, integrating cognitive, affective, and psychomotor aspects. The values inherent in Peresean can be integrated into formal education through a locally-based cultural approach, particularly in lessons that emphasize local wisdom. In conclusion, the Peresean tradition plays a crucial role in character formation in the Sasak community and should be incorporated into the educational curriculum as an effort to preserve culture and strengthen character education values in schools.